2021
DOI: 10.1051/0004-6361/202141198
|View full text |Cite
|
Sign up to set email alerts
|

A high pitch angle structure in the Sagittarius Arm

Abstract: Context. In spiral galaxies, star formation tends to trace features of the spiral pattern, including arms, spurs, feathers, and branches. However, in our own Milky Way, it has been challenging to connect individual star-forming regions to their larger Galactic environment owing to our perspective from within the disk. One feature in nearly all modern models of the Milky Way is the Sagittarius Arm, located inward of the Sun with a pitch angle of ∼12 • . Aims. We map the 3D locations and velocities of star-formi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 65 publications
5
16
0
3
Order By: Relevance
“…(See cautionary note by Bailer-Jones et al 2021, their Section 4.3. ) fid derived by Kuhn et al (2021b) using Gaia EDR3 -this distance is corroborated by our Chandra+Gaia analysis here. Nevertheless, the complicated molecular cloud velocity structure along the line of sight suggests the possibility of the coincidental alignment of multiple star-forming regions with differences distances.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…(See cautionary note by Bailer-Jones et al 2021, their Section 4.3. ) fid derived by Kuhn et al (2021b) using Gaia EDR3 -this distance is corroborated by our Chandra+Gaia analysis here. Nevertheless, the complicated molecular cloud velocity structure along the line of sight suggests the possibility of the coincidental alignment of multiple star-forming regions with differences distances.…”
Section: Introductionsupporting
confidence: 87%
“…Intriguingly, most of the rejected sources (7 out of 8) lie very close to the 3σ boundary. Given that the Trifid Nebula is part of a larger kpc-scale star-forming structure in the Sagittarius Arm (Kuhn et al 2021b), it is possible that some of these stars may be part of this larger scale structure, albeit not part of Trifid.…”
Section: Trifid Northmentioning
confidence: 99%
See 2 more Smart Citations
“…If we exclude the emission matching with Norma and 3-kpc arms, the filament is extending over 500 pc in the inter-arm region (assuming a minimum heliocentric distance of 4.5 kpc). Kuhn et al (2021) recently identified a 1 kpc, high pitch angle and high aspect ratio (7:1) structure associated with the Sagittarius arm. This feature is believed to be either an isolated entity, a sub-structure within the spiral arm or an inter-arm spur.…”
Section: Orientation Of the Gmf With Respect To The Spiral Armsmentioning
confidence: 99%